Perspectives for Sustainable Urban Transport Planning in Irkutsk - Engel, Barbara; Vogt, Walter (project baikal, 2015)
Mobility is a strong demand of urban societies and transport systems are backbones of urban life – in Russian cities like in other cities all over the world. Transport planning has to be understood as an integral part of urban development and urban planning. The report discusses problems and chances for sustainable urban transport planning in Irkutsk.